EVALUASI KONDISI LINGKUNGAN SEKOLAH BERBASIS MODEL DISCREPANCY DALAM MENDUKUNG PEMBELAJARAN DI SMA NEGERI 1 PADAIDO - Febrianti T. Lestari; Sukasno; Ahmad Muhibbin; Agus Susilo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to evaluate school environment conditions at SMA Negeri 1 Padaido using the Discrepancy Evaluation Model to identify gaps between ideal standards and actual conditions. In-depth interviews with twenty informants, 40 hours of participatory observation, and documentation study were employed using a qualitative approach with data collection through in-depth interviews with 29 informants, 40 hours of participatory observation, and documentation study. Data were analyzed using thematic analysis with MAXQDA 2022 software and validated through method triangulation and member checking. Results revealed significant discrepancies across five evaluation stages: design (22%), installation (34%), process (28%), product (31%), and cost-benefit (19%). The highest gaps were identified in sanitation facilities, with structural damage, and digital learning resource access, where only 28% of students have regular internet access. Based on Priority Index analysis, four priority intervention dimensions are sanitation-health facilities (PI=0.56), learning infrastructure (PI=0.41), social-emotional climate (PI=0.30), and digital access (PI=0.27). This research recommends developing medium-term development roadmaps, establishing a Quality Assurance Team, implementing participatory planning, and strengthening data-based advocacy to obtain adequate resource allocation for creating quality learning environments.